A new species of Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from western Yunnan, China - Guo, Weibo; Zhou, Kaiya; Yan, Jie; Li, Peng (Zootaxa, 2015)
A new species of the genus Hemiphyllodactylus is described from mountainous area of Changning County, Yunnan Province, China. Hemiphyllodactylus changningensis sp. nov. is distinguished from all other congeners by morphology and a significant genetic divergence of greater than 17% (ND2 gene). The new species from Changning is characterized by the following features: a maximum SVL of 40.1 mm in males and 43.8 mm in females; 11–15 dorsal scale rows; 6–8 ventral scale rows; a forefoot lamellar formula of 3-3/4-3/4-3; a hindfoot lamellar formula of 3-4-4-4 or 3-3-3-3; precloacal and femoral pore series continuous; cloacal spurs present in both sexes; dark dorsal transverse blotches; dark postorbital stripe; a brown postsacral mark bearing anteriorly projecting arms; and unpigmented caecum and gonads. The new species occurs also in Longyang District of Baoshan City, Yunnan Province, China.